Aesthetic values ​​of Islamic ceramic decorations Iznik ceramics as a model (Journal of the College of Basic Education, 2022)
After the exploratory study conducted by the researcher on a group of decorative formations that decorate Islamic ceramics in general and Ottoman ceramics in the city of Iznik in particular, with various materials and collectibles.The researcher raised a number of questions, including, what are the aesthetic values ​​that distinguished the Ottoman ceramics, especially in the city of Iznik, Turkey, from the rest of the other eras? Were these decorative values ​​of the Ottoman ceramics characterized by the pleasure that elevates the human taste towards renewal and inner insight beyond the decorative achievement, or is it a typical art that does not express precursors or a specific intellectual perspective? And did the aesthetic values ​​provide the aesthetic foundations and the ability to stimulate artistic and technical development in the field of decorating ceramic artifacts?